2016
DOI: 10.1186/s12913-016-1528-x
|View full text |Cite
|
Sign up to set email alerts
|

Cost of the medical management and prescription pattern for primary open angle glaucoma (POAG) in Ghana–a retrospective cross-sectional study from three referral facilities

Abstract: BackgroundGlaucoma is the leading cause of irreversible blindness globally, and treatment involves considerable cost to stakeholders in healthcare. However, there is infrequent availability of cost information and patterns of management, especially in developing countries. This study determined the cost of the medical management of POAG, adherence, and pattern of medication prescription in Ghana.MethodsA retrospective cross-sectional study involving 891 Primary Open Angle Glaucoma (POAG) cases seen in the year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 22 publications
8
31
2
Order By: Relevance
“…Even though sex did not play any role in glaucoma as illustrated in these studies [2,30], in our study there were more prescriptions given to female (52.7%%) than male (47.2%) clients. Similar result was reported in another study in Ghana [31] and other studies in India [32,33]. This calls for further and most probably larger studies to ascertain the role played by gender among Ghanaian patients with glaucoma.…”
Section: Cost Analysissupporting
confidence: 88%
See 2 more Smart Citations
“…Even though sex did not play any role in glaucoma as illustrated in these studies [2,30], in our study there were more prescriptions given to female (52.7%%) than male (47.2%) clients. Similar result was reported in another study in Ghana [31] and other studies in India [32,33]. This calls for further and most probably larger studies to ascertain the role played by gender among Ghanaian patients with glaucoma.…”
Section: Cost Analysissupporting
confidence: 88%
“…Finally our study showed that the highest cost of glaucoma treatment per prescription per annum is US$ 420. This is similar to a study done in Ghana [31] that looked amongst other things at the cost of glaucoma medications.…”
Section: Cost Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…There is a gradual shift from the use of beta-blockers as the first line of treatment for glaucoma in Ghana as prostaglandins analogs are now listed as essential drugs in Ghana and are therefore covered by the National Health Insurance Scheme [ 18 , 19 ]. That notwithstanding, there is still a comparable usage of beta-blockers ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of glaucoma cases reporting to a referral facility can therefore serve as a fair benchmark for evaluating the eye care-seeking behavior and the coverage of care for glaucoma. Available studies [ 11 18 ] in Ghana have amply dealt with the prevalence, risk factors, and to some extent the genetics of glaucoma but there remains a paucity of information on the epidemiology and clinical profile of patients living with glaucoma and receiving care in health care facilities. There is a recent study [ 19 ] on the epidemiological data among patients with Glaucoma and receiving care in a referral facility in the Ashanti region.…”
Section: Introductionmentioning
confidence: 99%